Generalized Granuloma Annulare Associated with Sjogren’s Syndrome: A Case Report - Wang H; Wang Y; Zheng Z; Cui Y (Clinical, Cosmetic and Investigational Dermatology, 2023)
Huijing Wang,1 Ying Wang,2 Zhancai Zheng,2 Yong Cui2 1Graduate School, Beijing University of Chinese Medicine, Beijing, People’s Republic of China; 2Department of Dermatology, China-Japan Friendship Hospital, Beijing, People’s Republic of ChinaCorrespondence: Ying Wang; Zhancai Zheng, Department of Dermatology, China-Japan Friendship Hospital, 2 Yinghua East Street, Chaoyang District, Beijing, 100029, People’s Republic of China, Tel +8618911977681 ; +8613501186450, Email dr_wy@hotmail.com; drzhengzhancai@163.comAbstract: Granuloma annulare (GA) is an uncommon disease in dermatology. Here, we report a case of generalized GA combined with Sjogren’s syndrome (SS) in a 65-year-old woman. To our knowledge, generalized GA combined with SS has not been reported before.Keywords: combination, case report, granuloma annulare, generalized skin lesions, Sjogren’s syndrome